2011
DOI: 10.3892/ijo.2011.1274
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of Human Leukocyte Antigen class I heavy chain in tumors is associated with a poor prognosis in advanced esophageal cancer patients

Abstract: The HLA class I antigen processing machinery (APM) plays a crucial role in the anticancer immune response. The aim of this study was to assess the clinical significance of APM components in esophageal cancer. A total of 11 esophageal cancer cell lines were evaluated by Western blot analysis for 13 HLA class I APM components. There was a different expression pattern among cancer cell lines for HLA class I heavy chain (HLA-HC), β2 microglobulin, Tapasin, TAP-1, TAP-2, LMP-7 and LMP-10. Immunohistochemical staini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 29 publications
0
36
0
1
Order By: Relevance
“…TMAs were constructed as described in our previous report (24). Patients without information about survival or broken and poor samples were omitted from analysis.…”
Section: Human Pdac Tissue Samplesmentioning
confidence: 99%
“…TMAs were constructed as described in our previous report (24). Patients without information about survival or broken and poor samples were omitted from analysis.…”
Section: Human Pdac Tissue Samplesmentioning
confidence: 99%
“…However, we observed that the percentage of CD8 + T cells exhibited a consistently positive correlation with the expression of TAP-1, TAP-2 and HLA-I, whereas the expression of IL-10 had a negative correlation with the expression of TAP-1, TAP-2 and HLA-I in NPC. These results suggest that the reduction in the expression of TAP-1, TAP-2 and HLA-I may contribute to the immunosuppression associated with in NPC, which may help tumor cells escape immune surveillance (20).…”
Section: Discussionmentioning
confidence: 85%
“…In terms of pancreatic cancer, Tewari et al[19] demonstrated a positive correlation between prognosis and the presence of tumor infiltrating T cells. Although the clinical relevance differs among types of cancer, in association with the HLA class I expression level[20], some agents have been reported to induce T-cell infiltration into pancreas cancers[21]. Homma et al[22] showed that CD4 + and CD8 + cells were significantly increased after neoadjuvant chemotherapy comprising gemcitabine and TS-1 followed by radiotherapy (NACRT), and a high accumulation of CD4 + cells offered a good prognostic marker for pancreas carcinoma after NACRT.…”
Section: Infiltrating T Lymphocytesmentioning
confidence: 99%